SAT0143 The arrest of bone mineral density loss at the lumbar spine and hip in patients with active rheumatoid arthritis during rituximab therapy. (12th June 2018) - Keywani, K.; Raterman, H. G.; ter Wee, M. M.; Nurmohamed, M. T.; Voskuyl, A. E.; Bultink, I. E.; Lems, W. F.
Abstract : Background: One of the well-known characteristics of rheumatoid arthritis (RA) is generalized bone loss. 1–2 Although rituximab is a frequently prescribed biologic disease-modifying anti-rheumatic drug (bDMARD) for the treatment of RA, data regarding changes in bone mineral density (BMD) in RA patients during rituximab therapy are limited. Objectives: To study the extent of BMD loss at lumbar spine and hip in patients with active rheumatoid arthritis treated with rituximab. Methods: Consecutive RA patients with an active disease status (DAS28>3.2) starting rituximab treatment were enrolled in a prospective cohort study. BMD of the lumbar spine and hip was measured before treatment and after one year using dual energy X-ray absorptiometry (DXA) to assess BMD changes. Clinical response was defined using the European League Against Rheumatism (EULAR) response criteria. Results: A total of 43 subjects (18.6% men) with mean age of 53.6 (SD 10.7) years were included in the study. Median disease duration was 9.5 (IQR 0.7–40.2) years and baseline mean DAS28 was 5.6 (SD 1.3). In responders, the DAS28 decreased with 1.97 points (SD 0.78) 95% CI 1.67 – 2.28 p<0.001; and in non-responders, the DAS28 decreased with 0.01 points (SD 0.67) 95% CI -0.35 – 0.37 p=0.945. All changes in BMD were not statistically significant (table 1). Conclusions: The findings of this study indicate that patients with active RA treated with rituximab have arrest of bone loss at both the lumbar spine and hip. Moreover, these results suggest that rituximab has bone-saving abilities even in the absence of clinical response. References: [1] McInnes IB, et al. The New England journal of medicine2011;365:2205–2219. [2] Firestein GS, et al. Nature2003;423:356–361. Disclosure of Interest: None declared